Shear and longitudinal modulus of elasticity in wood: relations based on static bending tests - Lahr, Francisco Antonio Rocco; Christoforo, André Luis; Varanda, Luciano Donizeti; Chahud, Eduardo; Araújo, Victor Almeida De; Branco, Luiz Antonio Melgaço Nunes (Acta scientiarum. Technology, 2017)
Improve quality of timber structures design is an aim that must be systematically sought by engineers in this area. An important topic that can contribute directly to be achieved in this subject is the more consistent knowledge related to structural properties of wood. Know values of longitudinal modulus of elasticity (E) and shear modulus (G) is essential for proper evaluation of plate structures performance, as example. It has been usual to adopt statistical equivalence for E and G values in plans longitudinal-radial and longitudinal-tangential, although experimental confirmation of this hypothesis is required. In this context, the aim of this work is to determine values of ELR, ELT, GLR and GLT, based on static bending tests, to five dicotyledonous species. Results showed statistical equivalence between the elastic properties in both plans, and the relation E = 35G was obtained for the five wood species here considered.